The Function of the Family in Shaping Children's Islamic Character in Indonesia: Systematic Literature Review - Satria, Hamzah; Samad, Duski; Zalnur, Muhammad (International Journal of Multidisciplinary Research of Higher Education, 2025)
The family has an important role as the first madrasah in forming children's Islamic character, educating them to become a generation with noble morals. This article aims to analyze the role and function of the family in shaping the Islamic character of children in Indonesia. This analysis was carried out using the Systematic Literature Review (SLR) method based on PRISMA guidelines by analyzing 14 articles indexed by Scopus. The results of the analysis found five main functions of the family in shaping children's Islamic character, namely: i) religious function, which teaches religious values ​​as the basis of life; ii) love and protection function, which provides affection and a sense of security; iii) socio-cultural function, which introduces Islamic norms and culture; iv) educational function, which guides children to learn Islamic values ​​v) socialization function of Islamic values, which instills good manners and morals. These functions significantly support the formation of children's Islamic character in accordance with the goals of national education and the Independent Curriculum, which encourages synergy between formal and non-formal education. This analysis also emphasizes the importance of collaboration between families and educational institutions to strengthen the role of the family. This analysis also recommends the development of family-based education policies to create an Islamic generation with good and noble character.